Knowledge on safe blood transfusion practice of senior staff nurses working in tertiary hospital - Nessa, Safarer; Faruquee, MH; Yasmin, Nawzia; Ahmed, Munir (Asian Journal of Medical and Biological Research, 2020)
Transfusion of blood saves life. An error in blood transfusion, at the same time, takes life. A cross sectional study was carried out for assessing the knowledge and practice on blood transfusion among the senior staff nurses using a structured questionnaire through face to face interview in Dhaka Medical College Hospital (DMCH). Among the about half of the respondents (54.8%)% were in the age group above 40 consisting 97.6% of female where 98% were married. By professional education 79% had Diploma in nursing and midwifery and 16.9% had graduation in nursing. This study revealed that the respondents could mentioned the name of screening tests as HBsAg (65.3%), HIV (58.1%), VDRL (53.2%), HBV (23.4%) and HBC (7.3%). Things to be checked and things to be considered also evaluated among the respondent and found responsive results. This study revealed that among the respondents 57% had moderate knowledge on blood transfusion, 41% good knowledge and only 2% had poor knowledge. There is an association between knowledge level on blood transfusion and year of service. This association is statistically not significant having p value 0.074. Among the respondents almost 48.4% stated transfuse screened blood as a preventive measure to fix problems regarding blood transfusion. Around 5.6% of the respondents mentioned maintaining proper system of blood transfusion as a measure. A few respondents (4.0%) said that difficulties due to blood transfusion can be prevented by controlling blood transfusion related side effects. The nurses practice self-protection of them and patient's protection during blood transfusion. There is needed of proper training on blood transfusion for prevention of complication in the patient as well as for the nurses themselves. Asian J. Med. Biol. Res. September 2020, 6(3): 587-593